2015
DOI: 10.1093/jnci/dju426
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Therapy in Lymph Node–Positive Vulvar Cancer: The AGO-CaRE-1 Study

Abstract: Background:Women with node-positive vulvar cancer have a high risk for disease recurrence. Indication criteria for adjuvant radiotherapy are controversial. This study was designed to further understand the role of adjuvant therapy in node-positive disease.Methods:Patients with primary squamous-cell vulvar cancer treated at 29 gynecologic cancer centers in Germany from 1998 through 2008 were included in this retrospective exploratory multicenter cohort study. Of 1618 documented patients, 1249 had surgical groin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
116
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 185 publications
(142 citation statements)
references
References 23 publications
(28 reference statements)
4
116
1
10
Order By: Relevance
“…Panici et al showed a correlation between age and OS, but not with DFS [34,35]. The relative survival, which is the difference in comparison with a non-affected sample patient group, was not analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Panici et al showed a correlation between age and OS, but not with DFS [34,35]. The relative survival, which is the difference in comparison with a non-affected sample patient group, was not analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the present analysis, patients with lymph node positive ratio ≤20% still received a benefit from chemotherapy, perhaps reflective of the persistent risk of distant microscopic disease in node-positive patients. Retrospective analyses from Germany and SEER have similarly argued for adjuvant radiotherapy in patients even with 1 involved lymph node, demonstrating a survival benefit [28,29]. Studies regarding the use of adjuvant chemotherapy for nodepositive vulvar cancer, either given concurrently with radiation or alone, are limited to small retrospective series [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In vulvar cancer however, often multiple, up to 7 SLN nodes per groin are identified 11 and are consequently excised to guide further groin treatment. 12,13 Thereby, morbidity potentially is increased with recurrent seroma, lymphedema, wound breakdown, or erysipelas despite of node-negative disease. Theoretically, the SLN with the highest isotope count (''hottest'' SLN) should be most likely to harbor tumor cells.…”
mentioning
confidence: 99%